Difference In Clinical & Biochemical Profile In Patients Of Long Standing Diabetes Having Diabetic Retinopathy & Patients Who Do Not Have Diabetic Retinopathy With Special Reference To Serum Bilirubin - Mehta, Jay; Gautam, Sunidhi; Patel, Tirtha; Kabra, Gunjan; Gore, Nikhil; D Ahir, Hasmukh; Singh, Punit (Journal of Neonatal Surgery, 2025)
e nanosized-based carrier systems which comprise solid lipid matrix combined with liquid lipids and surfactants. The aim of Diabetic retinopathy (DR) is a common complication of long-standing diabetes mellitus (DM) and is a leading cause of vision loss worldwide. Mounting evidence suggests that the presence of DR may be associated with alterations in various clinical and biochemical parameters, including serum bilirubin levels. This paper aims to explore the differences in the clinical and biochemical profiles of patients with long-standing DM, with and without DR, with a specific focus on serum bilirubin. Purpose: To study the association between serum bilirubin concentration and different grades of diabetic retinopathy in patients with type-2 diabetes mellitus Settings and Design: Cross sectional (observational) study Materials and Methods: A cross-sectional (observational) study was conducted among patients with duration of diabetes more than or equal to 3 years. Seventy-six eligible patients were undergone complete ophthalmic evaluation along with detailed Ocular and medical history followed by examination and measurements as described above. Diabetic gradings were done according to International Clinical Disease Severity Scale. All patients were grouped as without and with diabetic retinopathy changes using Early Treatment of Diabetic Retinopathy Study (ETDRS) classification. All patients were investigated to assess their glycaemic control (RBS and HbA1c) and serum bilirubin levels (Diazo method). Findings were recorded in a pre-designed proforma and analysed for relationship of biochemical parameters with various stages of diabetic retinopathy Results: The mean age of the study participants was 59.72 years. Among 7.9% had a duration of diabetes of more than ten years. 55.3% of the study participants had a duration of diabetes less than five years. In the present study, the mean total bilirubin was 0.58 mg/dl among diabetic patients. The mean values of direct and indirect bilirubin were 0.34 mg/dl (SD -0.14mg/dl) and 0.24 mg/dl (SD- 0.07 mg/dl), respectively. Conclusion: The proportion of diabetic retinopathy was significantly higher with long duration of diabetes. The mean values of total bilirubin, direct bilirubin and indirect bilirubin were significantly higher among the patients with no diabetic retinopathy compare to patients having diabetic retinopathy. Independent of conventional risk variables, low blood bilirubin concentrations were significantl related with an elevated risk of DR. Serum bilirubin may be used as a biomarker to identify persons at risk for DR.